Studies on the differentiation of T lymphocytes in sheep. II. Two monoclonal antibodies that recognize all ovine T lymphocytes. - Beya, M F (1986)
Two mouse monoclonal cytotoxic antibodies (ST-1a and ST-1b) recognize an antigen present on the large majority of thymocytes and all T cells in the periphery, but not B cells or other haemopoietic cells in sheep. Examination of frozen sections of various fetal tissues revealed that the cells expressing this antigen first appeared in the thymus, and these cells markedly increase in numbers in the peripheral lymphoid tissues after mid-gestation. Large accumulations of positive cells were located in the paracortex of lymph nodes, the periarteriolar lymphoid sheath of the spleen, and interfollicular areas of jejunal Peyer's patches, all of which are known to be T-dependent areas. Treatment of lymphocytes with ST-1a and complement resulted in the abrogation of T-proliferative responses, but the response to a B-cell mitogen, lipopolysaccharide, was not reduced. Neither ST-1a nor ST-1b cross-reacted to lymphocytes obtained from other species of animals (man, monkey, mouse, rat, guinea-pig, chicken, frog, pig, horse, goat and cattle). Based on these findings, it was concluded that the expression of the antigen recognized by ST-1a and ST-1b is restricted to the T-cell lineage of sheep, and that all ovine T cells express this antigen. Furthermore, ST-1a and ST-1b were determined to recognize the same antigen by reciprocal blocking experiments.